Construction and next-generation sequencing analysis of a large phage-displayed VNAR single-domain antibody library from six naïve nurse sharks. (7th November 2018) - Feng, Mingqian; Bian, Hejiao; Wu, Xiaolin; Fu, Tianyun; Fu, Ying; Hong, Jessica; Fleming, Bryan D; Flajnik, Martin F; Ho, Mitchell
ABSTRACT: Background: Shark new antigen receptor variable domain (VNAR ) antibodies can bind restricted epitopes that may be inaccessible to conventional antibodies. Methods: Here, we developed a library construction method based on polymerase chain reaction (PCR)-Extension Assembly and Self-Ligation (named "EASeL") to construct a large VNAR antibody library with a size of 1.2 × 10 10 from six naïve adult nurse sharks ( Ginglymostoma cirratum ). Results: The next-generation sequencing analysis of 1.19 million full-length VNAR s revealed that this library is highly diversified because it covers all four classical VNAR types (Types I–IV) including 11% of classical Type I and 57% of classical Type II. About 30% of the total VNAR s could not be categorized as any of the classical types. The high variability of complementarity determining region (CDR) 3 length and cysteine numbers are important for the diversity of VNAR s. To validate the use of the shark VNAR library for antibody discovery, we isolated a panel of VNAR phage binders to cancer therapy-related antigens, including glypican-3, human epidermal growth factor receptor 2 (HER2), and programmed cell death-1 (PD1). Additionally, we identified binders to viral antigens that included the Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS) spike proteins. The isolated shark single-domain antibodies including Type I and Type II VNAR s were produced in Escherichia coli and validated for their antigen binding. A Type II VNAR (PE38-B6) has a high affinity (Kd = 10.1 nM) for its antigen. Conclusions: The naïve nurse shark VNAR library is a useful source for isolating single-domain antibodies to a wide range of antigens. The EASeL method may be applicable to the construction of other large diversity gene expression libraries.